The Transcendental Obligations of Advocates and the Sustainability of Legal Representation: A Swiss Legal System Perspective - Titus Helmi, Teofilus; C. Adam, Richard (Universitas Islam Negeri Alauddin Makassar, 2026)
The practice of delegation through the granting of power of attorney is the cornerstone of the relationship between an attorney and a client; however, in reality, it is often confronted with the problem of protracted legal proceedings, which may result in the client’s death before their legal interests are resolved. This situation creates legal uncertainty regarding the continuation of the power of attorney as well as the fulfillment of the client’s interests, which are not merely material but also encompass a transcendent dimension that extends beyond the client’s physical existence. In Indonesian positive law, Article 1800 of the Civil Code affirms the obligation of the attorney-in-fact to continue handling the matter if the termination of the power of attorney has the potential to harm the principal. However, these provisions have not been accompanied by clear operational guidelines, even following the enactment of Law No. 18 of 2003 on Advocates, thereby creating room for inconsistencies in practice and interpretation. In contrast, Article 406 of the Swiss Code of Obligations provides a more explicit and systematic framework regarding the continuation of an attorney’s obligations following a client’s death. Through the comparative law method, this study finds that the client’s death does not automatically terminate the attorney’s obligations but rather reaffirms the professional and ethical duty to continue protecting the client’s legal interests until legal certainty is achieved. The theoretical contribution of this study lies in reinforcing the concept of the continuity of power of attorney based on the protection of legal interests after death, while simultaneously offering a conceptual foundation for the reform of power of attorney regulations in Indonesian law.